2017
DOI: 10.1097/ccm.0000000000002267
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Bicarbonate Versus Sodium Chloride for Preventing Contrast-Associated Acute Kidney Injury in Critically Ill Patients: A Randomized Controlled Trial

Abstract: Except for urinary pH, none of the outcomes differed between the two groups. Among ICU patients with stable renal function, the benefit of using sodium bicarbonate rather than isotonic sodium chloride for preventing contrast-associated acute kidney injury is marginal, if any.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 43 publications
0
21
0
1
Order By: Relevance
“…No study demonstrates protection of pre-emptive volume expansion against CA-AKI in the critically ill. An RCT comparing hydration with isotonic bicarbonate versus normal saline failed to show superiority of either regimen but reported an excessively high rate of CA-AKI of 33% in both groups [100], which may be attributed to severity of illness in this critically ill cohort. Importantly, in patients with chronic kidney disease (CKD) undergoing percutaneous coronary intervention (PCI), hydration volumes above 11 ml/kg body weight (BW) were associated with continuously increased rates of AKI, requirement for RRT and mortality.…”
Section: Volume Expansionmentioning
confidence: 99%
“…No study demonstrates protection of pre-emptive volume expansion against CA-AKI in the critically ill. An RCT comparing hydration with isotonic bicarbonate versus normal saline failed to show superiority of either regimen but reported an excessively high rate of CA-AKI of 33% in both groups [100], which may be attributed to severity of illness in this critically ill cohort. Importantly, in patients with chronic kidney disease (CKD) undergoing percutaneous coronary intervention (PCI), hydration volumes above 11 ml/kg body weight (BW) were associated with continuously increased rates of AKI, requirement for RRT and mortality.…”
Section: Volume Expansionmentioning
confidence: 99%
“…No RCTs, systematic reviews, or observational studies on alkalinisation compared to none were identified in our predefined population. A French multicenter RCT assessed sodium bicarbonate vs saline in the prevention of contrast‐induced AKI in critically ill patients in general and found no difference in patient‐important outcomes . In the PRESERVE trial 5177 high‐risk patients bound for angiography were randomised to 5 days of oral acetylcysteine and iv saline or intravenous bicarbonate using a 2‐by‐2 factorial design .…”
Section: Resultsmentioning
confidence: 99%
“…Also, we were not able to identify other trustworthy clinical practice guidelines on the topic. Our guideline holds limitations too: Our guideline is based on a very limited number of human observational studies of poor methodological quality, often with the use of “bundle‐therapies” including concomitant use of alkalinisation and mannitol, other diuretics or fluids . This made it difficult to discern treatment effects of individual therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Most meta-analyses before 2016 [79][80][81][82][83] confirmed that intravenous sodium bicarbonate was more effective than sodium chloride in preventing CI-AKI. However, two recent Journal of Interventional Cardiology 5 Journal of Interventional Cardiology 7 influential studies concluded that intravenous sodium bicarbonate provided no benefit over intravenous sodium chloride in high-risk patients [11] and critically ill patients [12]. Our NMA included 37 studies that compared intravenous sodium chloride with sodium bicarbonate, and our results also indicated that intravenous sodium bicarbonate led to a reduced risk for CI-AKI, although the effect size was small (OR [95% CI]: 0.74 [0.57, 0.93]).…”
Section: Discussionmentioning
confidence: 99%
“…Weisbord et al [11] enrolled 5177 high-risk patients and reported no benefit of intravenous sodium bicarbonate relative to normal saline. Another RCT [12] concluded that the benefit of sodium bicarbonate was marginal relative to isotonic sodium chloride for preventing CI-AKI among critically ill patients. However, other studies indicated that the Renal-Guard System [13][14][15][16] and hemodynamic guided hydration [17][18][19] were safe and effective in preventing CI-AKI.…”
Section: Introductionmentioning
confidence: 99%